chapter-header

RS Aggarwal Solutions Class 9 Mathematics Solutions for Factorization of Polynomials Exercise 3B in Chapter 3 - Factorization of Polynomials

Question 28 Factorization of Polynomials Exercise 3B

1 + 2𝑎𝑏 − (𝑎^2 + 𝑏^2)

Answer:

1 + 2𝑎𝑏 − (𝑎^2 + 𝑏^2)

We can further write it as

= 1 − (𝑎^2 + 𝑏^2 − 2𝑎𝑏)

So we get

= 1^2 − (𝑎 − 𝑏)^2

Based on the equation 𝑎^2 − 𝑏^2 = (𝑎 + 𝑏)(𝑎 − 𝑏)

We get,

= [1 + (a – b)][1 – (a – b)]

= (1 + a – b) (1 – a + b)

Connect with us on social media!
2022 © Quality Tutorials Pvt Ltd All rights reserved